Survival, by Birth Weight and Gestational Age, in Individuals With Congenital Heart Disease: A Population‐Based Study. Issue 7 (July 2017) - Best, Kate E.; Tennant, Peter W.G.; Rankin, Judith
Abstract : Background: Congenital heart disease (CHD) survival estimates are important to understand prognosis and evaluate health and social care needs. Few studies have reported CHD survival estimates according to maternal and fetal characteristics. This study aimed to identify predictors of CHD survival and report conditional survival estimates. Methods and Results: Cases of CHD (n=5070) born during 1985–2003 and notified to the Northern Congenital Abnormality Survey (NorCAS) were matched to national mortality information in 2008. Royston–Parmar regression was performed to identify predictors of survival. Five‐year survival estimates conditional on gestational age at delivery, birth weight, and year of birth were produced for isolated CHD (ie, CHD without extracardiac anomalies). Year of birth, gestational age, birth weight, and extracardiac anomalies were independently associated with mortality (all P ≤0.001). Five‐year survival for children born at term (37–41 weeks) in 2003 with average birth weight (within 1 SD of the mean) was 96.3% (95% CI, 95.6–97.0). Survival was most optimistic for high‐birth‐weight children (>1 SD from the mean) born post‐term (≥42 weeks; 97.9%; 95% CI, 96.8–99.1%) and least optimistic for very preterm (<32 weeks) low‐birth‐weight (<1 SD from mean) children (78.8%; 95% CI, 72.8–99.1). Conclusions: Five‐year CHD survival is highly influenced by gestational age and birth weight. For prenatal counseling, conditional survival estimates provide best‐ and worst‐case scenarios, depending on final gestational age and birth weight. For postnatal diagnoses, they can provide parents with more‐accurate predictions based on their baby's birth weight and gestational age.